UNSUR-UNSUR LOKALITAS DALAM NOVEL GALUH HATI KARYA RANDU ALAMSYAH (Locality Elements in Galuh Hati, Novel by Randu Alamsyah) - Agus Yulianto (Kantor Bahasa Sulawesi Tenggara, 2017)
Galuh Hati, novel written by Randu Alamsyah is one of novels that its background is in South Kalimantan area, especially the diamond mining at Cempaka. Therefore, it’s not surprising that this novel contains local color or people locality. Locality is actually an effort to make literary work down to earth. It makes a reader truly feels-not only physical background-but also a kind of culture system and social portrait from both explicit and implicit texts. The approach used in this research is sociology of literature. The aim of this study is to find out the elements of locality and social criticism in the story. Research problems are how the locality depicted in the novel Galuh Hati and what kind of social criticism found in the story. This study uses descriptive method with a library research. Based on the research, it is found that the locality in the novel includes the title, names of character and the using of local vocabulary in both narrative and dialogue. In addition, locality is also found in place and socio cultural setting.